Large-scale PV power generation in China: A grid parity and techno-economic analysis. (1st September 2017) - Zou, Hongyang; Du, Huibin; Brown, Marilyn A.; Mao, Guozhu
Abstract: With the limiting supply of fossil fuel and the beneficial impact of technological innovation on renewable energy costs, PV power generation is increasingly considered a promising way to generate renewable power. Under the support of the national emerging industry, China's PV industry has experienced a dramatic development over recent years, catapulting into a vital position in the world PV market. The newly installed PV capacity has led to cost reductions. This paper chooses the methodology of techno-economic evaluation to analyze current market application of residential PV power generation, including grid-connected and off-grid systems. One of the main innovations is choosing five Chinese cities in different areas of solar radiation as research objects, which enables regional differentiation in calculating levelized cost of energy (LCOE). The results show that grid-connected PV systems with 3 kW PV modules can meet the electric demand of a 60–90 m 2 residential building. The capacity of off-grid systems are 5–10 kW, which is determined by local solar radiation. By incorporating a learning curve, we forecast that off-grid PV systems for each of the five cities will reach grid parity over the next several decades. The estimation is used to offer policy recommendations for PV market diffusion in China. Highlights: Grid-connected and off-grid PV systems are examined by techno-economic evaluation. The levelized cost of energy (LCOE) of PV systems is calculated for five regions. The grid parity of PV power generation in China is estimated using learning curves. Grid parity varies across regions based on solar radiation and electricity prices. Policy implications are given to promote market deployment of China's PV industry.